Performance evaluation of multi-phase permanent magnet synchronous motor based on different winding configurations and magnetization patterns - M. Rezal; D. Ishak (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Permanent magnet synchronous motor (PMSM) is the most reliable and efficient machine that widely used in robotics and automation, industrial applications, electric vehicles, home appliances, aircraft and aerospace technology due to its high efficiency, good dynamic performance and high torque density. In this paper, the influence of various types of winding configuration and different magnetization patterns in the performance of a five-phase PMSM is investigated. Three types of magnetization patterns such as radial magnetization (RM), parallel magnetization (PaM), and multi-segmented Halbach magnetization (SH) are applied to the five-phase 10-slot/4-pole PMSM during open-circuit and on-load conditions. A 2D finite element method (FEM) is intensively used in this investigation to model and predict the electromagnetic characteristics and performance of the PMSM. The detailed results from the finite-element analysis (FEA) on the cogging torque, induced back-emf, airgap flux density and electromagnetic torque are analysed. The induced back-emf of the machine is computed further into its harmonic distortions. Additionally, the skewing method for minimization of cogging torque of PMSM is proposed. From the results, it is observed that the five-phase, 10-slot/4-pole PMSM with double layer distributed winding and parallel magnetization gives the best machine performance.